THE ROLE OF SELF-EFFICACY AND JOB INTEREST IN STUDENT WORK READINESS - Khoiriyah, Anita Nur; Faslah, Roni; Wolor, Christian Wiradendi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study investigates and assesses the extent to which self-efficacy and job interest influence students' readiness for entering the workforce. Employing a quantitative approach, the study involved 153 twelfth-grade Vocational High School students as participants. Data were analyzed through several stages, including validation and reliability testing of instruments, prerequisite tests for statistical analysis, application of multiple linear regression analysis, and hypothesis evaluation — executed with the assistance of IBM SPSS statistical tools. The findings reveal that: (1) Students’ readiness for the workforce is greatly and significantly influenced by their self-efficacy, (2) job interest also demonstrates a meaningful and positive impact, and (3) both variables together exert a significant and favorable influence on students' preparedness to transition for employment.